Escherichia coli in Brazilian Poultry Fecal Samples: Co-Carriage of Fosfomycin and ESBL Resistance - Felipe Juscele; Andre B. S. Saidenberg; Lars E. B. Christoffersen; Sofie M. Edslev; Søren Hallstrøm; Jessica R. Nacarato; Fernanda B. Barbosa; Marcos P. Cunha; Fernanda Esposito; Nilton H. Lincopan; Marc Stegger; Terezinha Knöbl (Antibiotics)
Background/Objectives: Fosfomycin, a critically important antibiotic, is widely used to treat urinary tract infections (UTIs) caused by multidrug-resistant (MDR) Escherichia coli, particularly those producing extended-spectrum β-lactamases (ESBLs). However, its increasing use in livestock has raised concerns about resistance development and global dissemination. This study investigated fosfomycin resistance in E. coli isolates from 400 fecal samples collected at Brazilian broiler farms. Methods: The samples were tested for their minimum inhibitory concentration (MIC), screened with PCR for specific resistance genes, and selected isolated were whole genome sequenced. Results: Phenotypic resistance to fosfomycin was detected in 19% (75/400) of the isolates, while the fosA3 gene, encoding enzymatic resistance, was identified in 4% (16/400) via PCR screening. Long-read sequencing of seven fosA3-positive isolates revealed the presence of fosA3 on IncFII and IncX plasmids, often co-located with blaCTX-M-55 within a conserved IS26-flanked transposon. Comparative genomic analysis of 133,541 global E. coli genomes from EnteroBase showed that 35% harbored similar transposon structures, with 2% carrying fosA3. These fosA3-positive isolates were significantly associated with South America and exhibited high co-carriage of ESBL genes, particularly in environmental and poultry-associated isolates. Phylogenetic analysis demonstrated no clustering by host or geographic origin, highlighting the global dissemination of these resistance determinants. Conclusions: Our findings emphasize the role of poultry production in the spread of fosfomycin and ESBL resistance, driven by transmissible plasmids and co-selection with third-generation cephalosporins. Improved antimicrobial stewardship, surveillance programs, and alternative management strategies are urgently needed to mitigate the dissemination of resistance and preserve fosfomycin’s efficacy in human medicine.